Assessing the Difference in Time to Increase Hemoglobin Levels at 1 hour, 6 hours, and 12 hours after Blood Transfusion in Thalassemia Patients at the Regional General Hospital Dr. Zainoel Abidin Banda Aceh - Riny Fasli; Heru Noviat Herdata; Dora Darussalam; Bakhtiar Bakhtiar; Sulaiman Yusuf; Syafruddin Haris; Rusdi Andid; Mulya Safri; Eka Destianti Edward (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Thalassemia is a congenital blood disorder characterized by reduced production of one or more globin chains. Thalassemia patients lack healthy hemoglobin which the body needs to be properly oxygenated. Blood transfusion is the main treatment for thalassemia patients. Checking hemoglobin levels after transfusion is a common test, but until now there is no definite uniformity of time to carry out these tests, so it will be detrimental to the patient and increase the length of the patient in the hospital. Assessing the difference in time to increase in hemoglobin levels at 1 hour, 6 hours, and 12 hours after blood transfusion in thalassemia patients. This research is an observational analytic study with cross sectional design. This study was conducted by examining the hemoglobin levels of thalassemia patients after 1 hour, 6 hours, and 12 hours after transfusion in thalassemia patients aged 1-18 years with a total sample of 40 people. The statistical analysis used was paired t test. The results showed that 20 men and 20 women and Most were in the age group 10-13 (35%), with an average Hb level at admission of 7.38 g / dL (95% CI). At 1 hour post-transfusion, the patient's mean Hb level increased by 8.97 g / dL (8,59-9,35 g / dL), at 6 hours post transfusion, 8.95 g / dL (8,57-9,32 g / dL), at 12 hours post transfusion increased by 9.60 g / dL (9,17-10,03 g / dL). Significant increase in Hb levels occurred at 1 hour and 12 hours after blood transfusion.